Bean Flower Thrips Megalurothrips usitatus (Bagnall) (Insecta: Thysanoptera: Thripidae) - Rafia Khan; Dakshina Seal; Rosan Adhikari (EDIS)
The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. Megalurothrips usitatus (Bagnall, 1913) is a small sized (3-4 mm) insect in the order Thysanoptera and family Thripidae, commonly known as bean flower thrips, oriental bean thrips, and Asian bean thrips. It is an important economic pest of legumes. Megalurothrips usitatus was first reported in the USA in Florida in 2020 (Soto-Adames, F. N. 2020).